Late Solitary Pancreatic Metastasis from Renal Cell Carcinoma: A Case Report. (26th June 2012) - Katsourakis, Anastasios; Noussios, George; Hadjis, Iosif; Alatsakis, Michael; Chatzitheoklitos, Efthimios
Abstract : We report a case of a 70-year-old man with renal cell carcinoma and metastasis to the pancreas. Symptomatic patients usually present with obstructive jaundice, abdominal pain, or GI bleeding. The diagnosis usually occurs in asymptomatic patients during followup for renal cell carcinoma. It usually befalls slowly from 2 to 18 years after the onset of the primary tumor of the kidney. A 70-year-old man presented in our department with weight loss, anorexia, and elevated blood glucose, having a large tumor on the head of the pancreas treated successfully by pancreatoduodenectomy. Three years after his treatment, the patient is doing well and without recurrence of the tumor. In conclusion, metastasis of renal cell carcinoma to the pancreas is a rare neoplasm accounting for 0.25–3% of all pancreatic tumors.